Impact of social deprivation, demographics and centre on HbA1c outcomes with continuous subcutaneous insulin infusion. Issue 3 (26th October 2018) - Paisley, A. N.; Beynon, J.; Fullwood, C.; Hindle, A.; Alam, T.; Urwin, A.; Chapman, A.; Morris, J.; Thabit, H.; Rutter, M. K.; Leelarathna, L.
Abstract: Aims: To assess the impact of social deprivation, demographics and centre on HbA1c outcomes with continuous subcutaneous insulin infusion (CSII) in adults with Type 1 diabetes. Methods: Demographic data, postcode‐derived English Index of Multiple Deprivation data and 12‐month average HbA1c (mmol/mol) pre‐ and post‐CSII were collated from three diabetes centres in the north west of England, University Hospital of South Manchester (UHSM), Salford Royal Foundation Hospital (SRFT) and Manchester Royal Infirmary (MRI). Univariable and multivariable regression models explored relationships between demographics, Index of Multiple Deprivation, centre and HbA1c outcomes. Results: Data were available for 693 (78%) individuals (UHSM, n = 90; SRFT, n = 112; and MRI, n = 491) of whom 59% were women. Median age at CSII start was 39 (IQR 29.5–49.0) years and median diabetes duration was 20 (11–29) years. Median Index of Multiple Deprivation was 15 193 (6313–25 727). Overall median HbA1c improved from 69 to 64 mmol/mol (8.5% to 8.0%) within the first year of CSII. In multivariable analysis, higher pre‐CSII HbA1c was significantly associated with higher deprivation ( P = 0.036), being female ( P < 0.001), and centre (MRI; P = 0.005). Following pre‐CSII HbA1c adjustment, post‐CSII HbA1c or HbA1c change were not related to demographic factors and deprivation, but remained significantly related to the centre; UHSM and SRFT had larger reductions in HbA1c with CSII compared with MRI [median −7.0 (−0.6%) vs. −6.0 (−0.55%) vs. −4.5 (−0.45%) mmol/mol; P = 0.005]. Conclusions: Higher pre‐CSII HbA1c levels were associated with higher deprivation and being female. CSII improves HbA1c irrespective of social deprivation and demographics. Significant differences in HbA1c improvements were observed between centres. Further work is warranted to explain these differences and minimize variation in clinical outcomes with CSII. What's new?: Continuous subcutaneous insulin infusion (CSII) is often considered the 'gold standard' of insulin replacement therapy for people with Type 1 diabetes. This is the first UK study to specifically report on the effects of social deprivation, demographics and centre on pre‐ and post‐CSII HbA1c levels. Those with higher social deprivation and women had higher baseline HbA1c levels. However, the benefits of CSII therapy were not found to be associated with social deprivation or demographics, only with pre‐CSII HbA1c and centre.